Analysis for financial management - Higgins, Robert C.; Koski, Jennifer L.; Mitton, Todd (New York McGraw Hill, 2019)
Analysis for Financial Management, 12e presents standard techniques and modern developments in a practical and intuitive manner with an emphasis on the managerial applications of financial analysis.
Index: 431-445 p.
Keywords: Tài chính - Ngân hàng.